CLINICAL UTILITY OF THE LICHTENBERG FINANCIAL DECISION MAKING RATING SCALE. (11th November 2018) - Gross, E; Rahman-Filipiak, A; Ficker, L; Lichtenberg, P
Abstract: The Lichtenberg Financial Decision Making Rating Scale (LFDRS) is an empirically validated measure useful for identifying impaired financial capacity and financial exploitation risk. Participants (n = 200, mean age = 71.5) completed the LFDRS. Clinicians rated financial decisional ability (FDA) for a personal decision and recorded suspected financial exploitation (SFE). Group differences were examined based on demographics and scores. ROC analyses were conducted to establish the clinical utility of LFDRS scales in identifying impaired FDA and SFE. Participants with impaired FDA were significantly older, less educated, and had higher risk scores. Participants with SFE had higher risk scores only. ROC analyses showed that the Intellectual subscale was the best correlate of impaired FDA, and the Total Score was the best correlate of SFE. Our results demonstrate the clinical utility of the LFDRS. Intellectual abilities are most important for decision making, but the full scale is needed to identify exploitation risk.